Cosolvent, ions, and temperature effects on the structural properties of cecropin A‐Magainin 2 hybrid peptide in solutions. Issue 1 (January 2015) - Sarukhanyan, Edita; Milano, Giuseppe; Roccatano, Danilo
ABSTRACT Antimicrobial peptides are promising alternative to traditional antibiotics and antitumor drugs for the battle against new antibiotic resistant bacteria strains and cancer maladies. The study of their structural and dynamics properties at physiological conditions can help to understand their stability, delivery mechanisms, and activity in the human body. In this article, we have used molecular dynamics simulations to study the effects of solvent environment, temperature, ions concentration, and peptide concentration on the structural properties of the antimicrobial hybrid peptide Cecropin A–Magainin 2. In TFE/water mixtures, the structure of the peptide retained α‐helix contents and an average hinge angle in close agreement with the experimental NMR and CD measurements reported in literature. Compared to the TFE/water mixture, the peptide simulated at the same ionic concentration lost most of its α‐helix structure. The increase of peptide concentration at both 300 and 310 K resulted in the peptide aggregation. The peptides in the complex retained the initial N‐ter α‐helix segment during all the simulation. The α‐helix stabilization is further enhanced in the high salt concentration simulations. The peptide aggregation was not observed in TFE/water mixture simulations and, the peptide aggregate, obtained from the water simulation, simulated in the same conditions did dissolve within few tens of nanoseconds. The results of this study provide insights at molecular level on the structural and dynamics properties of the CA‐MA peptide at physiological and membrane mimic conditions that can help to better understand its delivery and interaction with biological interfaces. © 2014 Wiley Periodicals, Inc. Biopolymers 103: 1–14, 2015.